Front Cover: Bimodal Probe for Magnetic Resonance Imaging and Photoacoustic Imaging Based on a PCTA‐Derived Gadolinium(III) Complex and ZW800–1 (Eur. J. Inorg. Chem. 29/2019). Issue 29 (10th July 2019) - Devreux, Marie; Henoumont, Céline; Dioury, Fabienne; Stanicki, Dimitri; Boutry, Sébastien; Larbanoix, Lionel; Ferroud, Clotilde; Muller, Robert N.; Laurent, Sophie
Abstract : The Front Cover shows a blood vessel containing the probe reported in this paper. The aim is to improve the image by combining photoacoustic imaging (PAI) and magnetic resonance imaging (MRI) by using a bimodal probe. The organic dye ZW800‐1 enables PAI thanks to its fluorescence in the near infrared (NIRF), and the gadolinium complex based on PCTA is ideal for MRI with radio‐frequency (RF) pulses. The combination leads to a precisely localized, high‐resolution bimodal image. More information can be found in the Full Paper by S. Laurent et al. For more on the story behind the cover research, see the Cover Profile .